NILAI – NILAI EKONOMI ISLAM KONFLIK HAK KEPEMILIKAN TANAH DAN ANCAMAN SATWA LIAR STUDI FENOMENOLOGI SOSIAL EKONOMI MASYARAKAT DESA PENYANGA HUTAN DI KECAMATAN SUOH KABUPATEN LAMPUNG BARAT - Asri Mutrikah; Rosydalina Putri; Alief Rakhman Setyanto (ITB AAS INDONESIA Surakarta, 2026)
Agrarian conflicts and human-wildlife interactions in forest buffer villages have become critical issues affecting community welfare, yet they are often examined separately and rarely integrated within an Islamic economics perspective. This study aims to analyze the relationship between land ownership conflicts and wildlife threats and their implications for the socio-economic resilience of communities in Suoh District, West Lampung Regency. This research employs a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observations, and documentation, and analyzed thematically through data reduction, data display, and conclusion drawing. The results indicate that uncertainty in land ownership status due to the disharmony between customary and formal legal recognition limits community access to economic resources, while wildlife disturbances reduce agricultural productivity and increase social risks. The novelty of this study lies in integrating agrarian conflict and human–wildlife conflict within a phenomenological framework based on Islamic economic values. The findings also reveal adaptive strategies developed by communities through social solidarity, collective resource management, and local deliberation to strengthen socio-economic resilience.